Business ethical perceptions of business people in east China: an empirical study. - Wu, Xinwen (Business Ethics Quarterly, 1999)
A study was conducted to examine the ethical perceptions of businesspeople and the current state of business ethics in east China. Data were drawn from a survey of 800 businesspeople in 59 enterprises and interviews with 42 senior executives. Findings reveal that business ethics is a new and popular topic in east China and that there exists widespread pessimism among businesspeople about ethical standards among their superiors and coworkers and about the ethical climate of their businesses. Findings also reveal that awareness of the importance of business ethics is growing among business leaders and that the development of a market economy and the improvement of business ethics will go hand-in-hand. In addition, findings indicate that businesspeople in east China have varying ethical perceptions and that business ethics in east China are currently complex and prone to change.